Spain in the Arctic (Spanish Yearbook of International Law, 2012)
As the 21st century unfolds, the Arctic sea-ice has been undergoing an unprecedented transformation leading to renewed international scrutiny of the Arctic Ocean. Faced with this renewed scrutiny of the Arctic, this study focuses on current Spanish interests in the Arctic. They are concerned basically, on the one hand, with the interpretation and application of the 1920 Svalbard Treaty regarding the Svalbard maritime zones, and, on the other hand, with Spanish position as Observer State in the Arctic Council towards an analysis on the scientifĳic impact on Arctic political matters, but without forgetting the emerging presence of the European Union of which Spain is a member State.